Leader–Member Exchange, Work Commitment, And Personnel Performance: The Moderating Role Of Job Satisfaction - Renaldo Sau Galla (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the influence of Leader-Member Exchange (LMX) and work commitment on personnel performance, as well as examine the role of job satisfaction moderation in strengthening these relationships within the South Sulawesi Regional Police. Using a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS), this study involved 240 police personnel selected through purposive sampling techniques. The results of the measurement model test showed that all research instruments met strict validity and reliability criteria. The results of the hypothesis test revealed that LMX has a positive and significant influence on work commitment and personnel performance. Similarly, work commitment has been shown to have a significant effect on performance improvement. However, it was found that job satisfaction did not have a significant direct influence on personnel performance. Interestingly, the results of the moderation test showed that job satisfaction played a significant role as a moderator variable that strengthened the influence of work commitment on performance. These findings confirm that to achieve optimal organizational performance, the South Sulawesi Regional Police needs to pay attention to the quality of superior-subordinate relationships and create a satisfactory work environment to convert personnel commitments into real performance.